2023
DOI: 10.1002/hed.27342
|View full text |Cite
|
Sign up to set email alerts
|

Fascial layers encountered in the lateral skull base region: A cadaveric and radiological analysis

Abstract: Background In our experience, the anterior carotid sheath forms an important plane of dissection when excising temporal bone region cancers. However, its anatomical composition, relationships, and radiological appearance remains unclear. Methods Eight sides of cadaveric heads were dissected. Anatomical findings were correlated with a high‐resolution baseline T1 MRI. Results The anterior carotid sheath was formed by the tensor‐vascular‐styloid fascia, stylopharyngeal fascia, buccopharyngeal fascia (BPF), and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, through using the styloid process as a surrogate landmark from which this plane attaches, as demonstrated in our previous anatomical study, some conclusions could still be drawn. 15 We found that only few tumors (n = 6/54, 11.1%) extended medially to erode or encase the styloid, and thus breached the anterior carotid sheath. A larger proportion of patients (n = 20, 37.0%) had tumors that were situated close (≤5 mm) to or abutting the styloid process.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…However, through using the styloid process as a surrogate landmark from which this plane attaches, as demonstrated in our previous anatomical study, some conclusions could still be drawn. 15 We found that only few tumors (n = 6/54, 11.1%) extended medially to erode or encase the styloid, and thus breached the anterior carotid sheath. A larger proportion of patients (n = 20, 37.0%) had tumors that were situated close (≤5 mm) to or abutting the styloid process.…”
Section: Discussionmentioning
confidence: 65%
“…[10][11][12][13][14] As an initial step, we conducted anatomical cadaveric dissections to further our understanding of the fascial planes in the lateral skull base region. 15 We found a thick fascial plane forming the anterior carotid sheath at the skull base (Figure 1), which could also be identified on high-resolution 3T magnetic resonance imaging (MRI). In our clinical experience, this fascial layer forms a very useful plane of dissection when excising tumors in this region, protecting the major vessels and lower cranial nerves from injury.…”
mentioning
confidence: 71%
See 2 more Smart Citations